Greater risk for frequent marijuana use and problems among young adult marijuana users with a medical marijuana card. (1st January 2019) - Tucker, Joan S.; Rodriguez, Anthony; Pedersen, Eric R.; Seelam, Rachana; Shih, Regina A.; D'Amico, Elizabeth J.
Highlights: Among 671 young adult marijuana users, 28% had a medical marijuana (MM) card. MM card holders were more likely than others to be frequent users from ages 13–19. MM card holders reported more consequences and problem behaviors in young adulthood. Differences were found after matching groups on sociodemographic characteristics. Abstract: Background: This study compared young adults with and without a medical marijuana (MM) recommendation from a provider ("MM card") on their developmental trajectories of frequent marijuana use and marijuana-related problems in young adulthood. Methods: The analytic sample consists of young adult past month marijuana users ( N = 671) who were part of a larger, diverse, and predominantly California cohort. Analyses are based on data from seven surveys completed from ages 13–19. Results: At age 19, 28% of participants reported having an MM card to legally purchase marijuana from an MM dispensary. A multiple group latent growth model indicated that young adults who had an MM card showed steeper increases in frequent marijuana use (i.e., 20–30 days of use in the past month) from ages 13–19 compared to young adults who did not have an MM card. Logistic regression models that matched MM cardholders and non-MM cardholders on individual sociodemographic characteristics found that MM cardholders were more likely to report marijuana negative consequences, selling marijuana/hashish, and driving under the influence of marijuana in the past year. In addition, MM cardholders were more likely to have tried cutting down or quitting in the past 3-months. Conclusions: Among young adult marijuana users, those with an MM card had a higher risk profile for marijuana use and related problems compared to those without an MM card. Given expanding state legalization of MM, this issue warrants further attention.